Targeting PLK1 as a novel chemopreventive approach to eradicate preneoplastic mucosal changes in the head and neck - de Boer, D Vicky; Martens-de Kemp, Sanne R; Buijze, Marijke; Stigter-van Walsum, Marijke; Bloemena, Elisabeth; Dietrich, Ralf; Leemans, C René; van Beusechem, Victor W; Braakhuis, Boudewijn J M; Brakenhoff, Ruud H (Oncotarget, 2017)
Head and neck squamous cell carcinomas (HNSCC) and local relapses thereof develop in preneoplastic fields in the mucosal linings of the upper aerodigestive tract. These fields are characterized by tumor-associated genetic changes, are frequently dysplastic and occasionally macroscopically visible. Currently, no adequate treatment options exist to prevent tumor development. Array-based screening with a panel of tumor-lethal small interfering RNAs (siRNAs) identified ( ) as essential for survival of preneoplastic cells. Inhibition of PLK1 caused cell death of preneoplastic and HNSCC cells, while primary cells were hardly affected. Both siRNAs and small molecule inhibitors caused a strong G2/M cell cycle arrest accompanied by formation of monopolar spindles. In a xenografted mouse model PLK1 caused a significant tumor growth delay and cures, while chemoradiation had no effect. Thus, PLK1 seems to be a promising target for chemopreventive treatment of preneoplastic cells, and could be applied to prevent HNSCC and local relapses.